Composition and floristic characteristics of national key protected wild plants distributed in Hainan Province, China - LI Jinghan, ZHANG Shunwei, YANG Xiaobo*, LI Donghai, QI Chunlin, HUANG Yao, ZHANG Xiang, HAO Jiewei, LIANG Caiqun, ZHU Zicheng, JIANG Yuexin, WANG Chongyang, HE Yiqi (Guangxi Zhiwu)
Based on the List of National Key Protected Wild Plants and related data in 2021, combined with field investigation, the List of National Key Protected Wild Plants in Hainan Province was integrated, and its composition and floristic characteristics were analyzed. The results were as follows:(1)Among the national key protected wild plants, the original Cycas changjiangensis, C. hainanensis, C. lingshuigensis and C. taiwaniana were incorporated into C. taiwaniana; compared with the List of National Key Protected Wild Plants in 1999, the original Semiliquidambar cathayensis and Amphicarpaea linearis were removed from the protection level, and Bretschneidera sinensis was degraded from Category I protection to the Category Ⅱ protection. A total of 127 species of national key protected wild plants were added, and a total of 173 species(including varieties)with the addition of original, belonging to 53 families and 83 genera, including 8 species of national Category I protected wild plants. There were 165 species of national Category Ⅱ protected wild plants and 32 endemic species in Hainan Province, which belonging to four groups. Among them, the angiosperm species were the most abundant, with 129 species.(2)Based on years of field investigation information and the results of this survey, C. rumphii, C.shanyagensis, Alsophila costularis and Paphiopedilum purpuratum had not been investigated.(3)The life forms of 173 protected plants were divided into five types, mainly phanerophytes(115 species), followed by hemicryptophytes(34 species)and geocryptophytes(22 species), and chamaephytes and cushion plant were the least(1 species).(4)At the family level, Orchidaceae had the largest number of species, including 47 species(27.17%). At the genus level, Dendrobium had the largest number of species, including 21 species(12.14%).( 5 )The floristic elements were complex and had obvious tropical characteristics. The families were mainly distributed in the pantropics and their variants. The genera were mainly distributed in tropical Asia and its variants. In summary, the tropical nature and unique phenomena of national key protected wild plants in Hainan Province are obvious, and there are many new protected species. Therefore, background investigation and dynamic monitoring should be carried out continuously, law enforcement should be strengthened, human factors should be reduced to interfere with and destroy habitats, and in-situ and ex-situ protection measures should be taken to strengthen protection and management.